Bovine Lactoferrin-Loaded Plasmonic Magnetoliposomes for Antifungal Therapeutic Applications - Mélanie Pereira; Ana Rita O. Rodrigues; Leslie Amaral; Manuela Côrte-Real; Cátia Santos-Pereira; Elisabete M. S. Castanheira (MDPI AG, 2023)
Bovine lactoferrin (bLf) is a milk-derived protein that exhibits potent broad-spectrum antifungal activity against multiple fungi. bLf is susceptible to degradation, while some of its properties depend on the tertiary structure. So, the encapsulation of bLf in stimuli-responsive therapeutic formulations provides an added value to enhance its biological activities. Plasmonic magnetoliposomes (PMLs) arise as promising nanocarriers for dual hyperthermia (magneto-photothermia) and local chemotherapy, since the combination of magnetic and gold nanoparticles (NPs) in a single nanosystem (multifunctional liposomes) enables the targeting and controlled release of loaded drugs. In this work, plasmonic magnetoliposomes (PMLs) containing manganese ferrite nanoparticles (28 nm size) and gold nanoparticles (5-7.5 nm size), functionalized with 11-mercaptoundecanoic acid or octadecanethiol, were prepared and loaded with bLf. The NPs' optical, magnetic and structural properties were measured via UV/vis/NIR absorption spectroscopy, SQUID and TEM, respectively. The Specific Absorption Rate (SAR) was calculated to assess the capabilities for magnetic and photothermal hyperthermia. Finally, the antifungal potential of bLf-loaded PMLs and their mechanism of internalization were assessed in Saccharomyces cerevisiae by counting the colony forming units and using fluorescence microscopy. The results demonstrate that PMLs are mainly internalized through an energy- and temperature-dependent endocytic process, though the contribution of a diffusion component cannot be discarded. Most notably, only bLf-loaded plasmonic magnetoliposomes display cytotoxicity with an efficiency similar to free bLf, attesting their promising potential for bLf delivery in the context of antifungal therapeutic interventions.